تحليل العوامل الحرجة المؤثرة على إنتاجية العمالة في صناعة التشييد - ماهر عوض (Tishreen University, 2018)
تؤثر الإنتاجية على كل قيود المشروع و هي عامل هام لنجاح المشروع. یستعرض هذا البحث العوامل المؤثرة في انتاحیة العمالة في مشاریع التشیید السورية. الهدف من هذا البحث هو تحديد الأسباب المؤثرة على إنتاجية العمالة و من ثم ترتيب هذه الأسباب بالاعتماد على عامل الأهمية النسبية أو عامل الخطورة لكل عامل. تم تحديد العوامل المؤثرة على نقص الإنتاجية من خلال مراجعة العديد من الدراسات السابقة و اجراء بعض المقابلات مع مدراء مشاريع في الشركات العاملة في محال صناعة التشييد، و بذلك تم تحديد 76 عامل هي الاكثر تأثيرا على انخفاض انتاجية العمالة في مشاريع التشييد السورية، بعد ذلك  تم القیام بمسح میداني من خلال تصميم الاستبیان المناسب حيث تم الحصول على 52 استمارة صالحة للتحليل. تم استخدام طريقة مؤشر الأهمية النسبية أو درجة الخطورة لترتيب أسباب تدني إنتاجية العمالة. قد خلصت الدراسة الى أن اهم الأسباب المؤثرة في انتاجیة العمالة هي: تدني الرواتب، و عدم توفر المواد, و الظروف المالية  للمقاول، و نقص تعليات السلامة، و حجم ورشة، و قلة المكافآت، و التأخر في صرف الكشوف، و نقص التدريب، و مدى ملائمة ترتيب التنفيذ، و قلة الحوافز. Poor productivity of construction workers is one of the causes of cost and time overruns in construction projects. Productivity plays an important role in the construction industry. Productivity is one of the most important issues in both developed and developing countries. This paper reports an investigation of the productivity problems in Syrian construction projects through a structured questionnaire survey. The main objective of this study is to determine and rank the factors that affecting labour productivity. 76 factors were identified through a detailed literature review and interview with projects managers. a questionnaire survey was designed and distributed to staff of various construction companies. The data obtained was analysed using the relative importance index. The results from the analysis revealed ten major factors affecting labour productivity in Syrian construction industry. These factors are: poor salary, material shortage, financial condition of contractor, poor safety instructions, size of workshop, rewards shortage, payment delay, low training, and low incentives.